The Politics of Distributing Social Transfers: State Capacity and Political Contestation in Sub-Saharan Africa and South Asia - Tom Lavers (Oxford University Press, 2022)
This book provides a systematic analysis of the political processes shaping the distribution of social transfers in six countries in sub-Saharan Africa and South Asia. In doing so, the book addresses a notable gap in recent research on social protection concerning the politics of implementation. While considerable attention has been devoted to debating the merits of different policy designs and the political factors shaping the adoption and diffusion of different policy models, ultimately the ability of any social transfer programme to deliver on its promises is dependent on the effective implementation and distribution of social transfers in line with intended objectives. The chapters in this book examine international and sub-national variation in programme implementation in Bangladesh, Ethiopia, Ghana, Kenya, Nepal, and Rwanda, drawing on a common analytical framework that highlights the importance of state capacity and reach, rooted in histories of state formation, and contemporary political competition in shaping the distribution of social transfers. Comparative analysis of the case studies supports the view that variation in the capacity and reach of the state within countries is a centrally important factor shaping the effectiveness and impartiality of distribution. Yet state capacity alone is insufficient. Rather, political competition and power relations shape how this capacity is actually deployed in practice. As such, the book underscores the inherently political nature of implementation and questions common technocratic efforts to improve implementation by de-politicizing the social protection policy process.
Keywords: 330; social protection; social transfer; policy implementation; political economy; power relations; state capacity; Africa; South Asia